UJI KERAGAMAN GENETIK, HERITABILITAS DAN KERAGAAN AGRONOMI GALUR F6 PADI TIPE BARU HITAM DAN MERAH DATARAN TINGGI - Parari, Trisday Yiin; Limbongan, Yusuf L; Mangando, Yeheskiel; Karamang, Syukur (Universitas Islam Madura, 2024)
Efforts to increase rice production in the highlands which are hampered by cold temperatures continue to be made, one of which is by developing new varieties that are able to adapt to these conditions. The aim of this research was to test genetic diversity, heritability values, and test the performance of agronomic characters of several new types of F6 black and red rice resulting from crosses. This research was carried out in rainfed rice fields in Barana' Hamlet, Tikala District, North Toraja Regency at an altitude of 855 m above sea level. This research took place from May 2023 to December 2024. The planting material used in this research consisted of 6 promising F6 lines of black and red rice as well as the comparisons Inpari 4, Pare Lea, Pare Ambo and Pare Lallodo. This panel research was structured in the form of a randomized block design (RAK) with 3 replications so that there were 18 experimental plots. Each plot consists of 6 planting rows. The variables observed consisted of agronomic character components and organoleptic tests. Data analysis used analysis of variance (Anova) and the BNJ test level was 0.05. The results of the research show that the value of genetic diversity and phenotypic character of the new types of black and red F6 rice lines shows narrow criteria. The characteristics of the number of grain contents per panicle, weight of 100 seeds, panicle length and number of productive tillers had the best genetic diversity coefficient values. All the characters of the new black and red types of F6 rice lines have broad heritability values and high KGH. UKIT101-2-278-4, UKIT105-2-042-3 and UKIT105-2-042-5 lines had the best agronomic characteristics in terms of harvested dry grain weight per hectare, number of filled grains per panicle and number of productive tillers. UKIT101-2-278-2 and UKIT101-2-278-4 strains have rice in the criteria of the best taste and aroma.